ChemInform Abstract: Recent Advances in Transition Metal (Pd, Ni)‐Catalyzed C(sp3)H Bond Activation with Bidentate Directing Groups. Issue 18 (April 2016) - Yang, Xinglin; Shan, Gang; Wang, Liguo; Rao, Yu
Abstract: Review: [85 refs.